Study of iron based magnetocaloric nanomaterials - Chaudhary, Varun (Nanyang Technological University, 2020)
Magnetic materials experience a change in temperature when they are adiabatically magnetized and demagnetized, this phenomena is known as the magnetocaloric effect (MCE). The MCE can be employed in environmentally friendly, green and novel energy efficient cooling systems as this technique does not have hydrofluorocarbons or ozone depleting gases, unlike conventional gas compression cooling systems. The giant MCE in rare earth based materials has motivated magnetocaloric research in the last two decades. However, the systems studied so far, i.e., gadolinium based materials are very expensive, corrode easily and have limited availability. Developing a new, affordable, readily available and corrosion resistant material is desired for commercial use. Low relative cooling power (RCP) is often another challenge in developing a magnetic cooling system. Nanoparticles can increase the working temperature span, therefore we developed transition metal based magnetocaloric nanoparticles which are environmentally friendly, affordable and possess RCP higher than those of gadolinium nanoparticles.